ANALISIS PENERAPAN PRINSIP KEADILAN DALAM HUKUM WARIS ISLAM DAN IMPLEMENTASINYA DI MASYARAKAT - Harahap, Taufik Hidayat (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
This study aims to analyze the application of the principle of justice in Islamic inheritance law and its implementation in the distribution of inheritance assets in society. Islamic inheritance law stipulates that the distribution of inheritance should be based on the rights and responsibilities of each heir, but the public's understanding of this principle is still limited. Many individuals assume that justice in inheritance distribution means equal shares, without considering the differing responsibilities between men and women, such as the obligation of men to provide for their families. This research uses a qualitative approach with library research and case study methods. The library research involves gathering literature on Islamic inheritance law, while the case study involves observing inheritance distribution practices in society. The findings of the study indicate that inheritance distribution practices often do not align with the principles of Islamic inheritance law, mainly because communities tend to follow customary laws or family traditions. This can lead to injustice and conflicts among heirs. Therefore, this research emphasizes the importance of wider socialization and education on Islamic inheritance law so that the public can understand and apply it correctly. With better understanding, it is hoped that inheritance distribution can be carried out justly and harmoniously, in accordance with the principle of justice in Islam.